Amyand's hernia in neonate: a case report - Ab. Rahman, Norhafiza; Gunasekar, Samuel; Ahmad Lela, Alia Maisyah (2014)
Amyand's hernia is a condition in which vermiform appendix present in the inguinal hernia sac. It is a rare entity, even so in children and neonates. The presentation is often similar like obstructed or strangulated inguinal hernia in which patient came in with tender, often irreducible inguinal swelling. Pre-operative diagnosis is usually difficult and in majority of patients, the correct diagnosis is only made intra-operatively. The difficult pre-operative diagnosis, however, does not affect the management in most cases as the affected patients are usually posted for emergency hernia repair immediately after presentation. We are presenting a case of an Amyand's hernia that occured in a neonate who presented on day 8 of life with sudden onset of right sided inguinal swelling. He was brought in early by the parents and posted urgently for surgery. Intra-operative finding revealed Amyand hernia with gangrenous appendix which was subjected to herniotomy and appendicectomy.